Daily Dynamics of Gas Exchange and Photosynthetic Pigments in Green Algae. Chlamydomonas parientaria - N.K.Kozirakhimovа; N.M.Dushaeva; M.Kh.Khamidjonova; M.M.Bobokhonov (Genius Publishing Group, 2023)
Algological studies include the study of physiological processes of promising algae from the point of view of productivity. In order to achieve high productivity, algae are grown in intensive laboratory conditions, which are accompanied by changes in the amount of gas exchange processes and photosynthetic pigments. The study of this nature is necessary to determine the processes of adaptation to changes in external conditions, as well as to determine the dependence of the photosynthesis apparatus on light. Productive strains are characterized by high photosynthesis and lability of photosynthetic apparatus capable of ensuring high productivity of microalgae. The ratio of photosynthetic pigments characterizes the physiological state of cell culture and is related to the operation of photosystems I and II of photosynthesis
Keywords: daily dynamics of microalgae photosynthesis; gas exchange; activity